Bearing capacity of cold-formed unlipped channels with restrained flanges under EOF and IOF load cases - Janarthanan, B.; Mahendran, M.; Gunalan, S. (Ernst & Sohn Verlag für Architektur und technische Wissenschaften GmbH & Co. KG, Berlin, 2015)
Bearing failure is a form of localized failure that occurs when thin-walled cold-formed steel sections are subjected to concentrated loads or support reactions. To determine the bearing capacity of cold-formed channel sections, a unified design equation with different bearing coefficients is given in the current North American specification AISI S100 and the Australian/New Zealand standard AS/NZS 4600. However, coefficients are not available for unlipped channel sections that are normally fastened to supports through their flanges. Eurocode 3 Part 1.3 includes bearing capacity equations for different load cases, but does not distinguish between fastened and unfastened support conditions. Therefore, an experimental study was conducted to determine the bearing capacities of these sections as used in floor systems. Twenty-eight web bearing tests on unlipped channel sections with restrained flanges were conducted under End One Flange (EOF) and Interior One Flange (IOF) load cases. Using the results from this study, a new equation was proposed within the AISI S100 and AS/NZS 4600 guidelines to determine the bearing capacities of cold-formed unlipped channels with flanges fastened to supports. A new design rule was also proposed based on the direct strength method.
Keywords: Cold‐formed unlipped channel sections; bearing capacity